MOTIVATING ENGLISH TEACHERS BASED ON THE BASIC NEEDS THEORY AND AN EXPECTANCY THEORY - Hidayatus Sholihah (Universitas Islam Sultan Agung, 2017)
There are two main motivation theories. a hierarchy of basic needs theory, and an expectancy theory. In a Hyrarchy of basic needs theory, Maslow has stated that the basic needs as a main behaviour direction are structured into a hierarchy. There are five basic human needs. The first: Physiological needs such as: salary, bonus or working condition. The second: the safety needs, such as: safe job environment, job security or health cover. The third, social needs, such as union and team work. The next is self esteem, such as getting an award, medal, certificate or any other recognisition. Then the last is self actualization, for example is by providing an opportunity to share knowledge, skills and eprerience. The evaluation of this theory are: there is no spiritual needs as human basic needs is a main weakness of this theory. Then it is possible that different level of needs have to be satisfied in the same time, or not in hierarchy level or, not always have to be fulfilled in order. The next motivation theory is an Expectancy Theory. This theory is based on three main factors. The first factor is: English teachers will be motivated to work harder if they have a good perception to their own competences in accordance with their job. The second, individual motivation depends on the rewards given when they finish a particular job. Finally, it also depends on their regards to the rewards given from the job that they do. Expectancy theory is a good theory, however, it is not easy to be implemented because the principals should provide various types of reward to satisfy the expectation of their English teachers. Considering the strengths and weaknesses of these two theories, it is better to combine both of them in the practice to get more effective results.